The effect of dulaglutide on stroke: an exploratory analysis of the REWIND trial. Issue 2 (February 2020) - Gerstein, Hertzel C; Hart, Robert; Colhoun, Helen M; Diaz, Rafael; Lakshmanan, Mark; Botros, Fady T; Probstfield, Jeffrey; Riddle, Matthew C; Rydén, Lars; Atisso, Charles Messan; Dyal, Leanne; Hall, Stephanie; et al.
Summary: Background: Cardiovascular outcome trials have suggested that glucagon-like peptide 1 (GLP-1) receptor agonists might reduce strokes. We analysed the effect of dulaglutide on stroke within the researching cardiovascular events with a weekly incretin in diabetes (REWIND) trial. Methods: REWIND was a multicentre, randomised, double-blind, placebo-controlled trial done at 371 sites in 24 countries. Men and women (aged ≥50 years) with established or newly detected type 2 diabetes whose HbA1c was 9·5% or less (with no lower limit) on stable doses of up to two oral glucose-lowering drugs with or without basal insulin therapy were eligible if their body-mass index was at least 23 kg/m 2 . Participants were randomly assigned (1:1) to weekly subcutaneous injections of either masked dulaglutide 1·5 mg or the same volume of masked placebo (containing the same excipients but without dulaglutide). Randomisation was done by a computer-generated random code with an interactive web response system with stratification by site. Participants, investigators, the trial leadership, and all other personnel were masked to treatment allocation until the trial was completed and the database was locked. During the treatment period, participants in both groups were instructed to inject study drug on the same day at around the same time, each week. Strokes were categorised as fatal or non-fatal, and as either ischaemic, haemorrhagic, or undetermined. Stroke severity was assessed using the modified Rankin scale. Participants were seen at 2 weeks, 3 months, 6 months, and then every 3 months for drug dispensing and every 6 months for detailed assessments, until 1200 confirmed primary outcomes accrued. The primary endpoint was the first occurrence of any component of the composite outcome, which comprised non-fatal myocardial infarction, non-fatal stroke, or death from cardiovascular or unknown causes. All analyses were done according to an intention-to-treat strategy that included all randomly assigned participants, irrespective of adherence. The trial is registered with ClinicalTrials.gov, number NCT01394952 . Findings: Between Aug 18, 2011, and Aug 14, 2013, we screened 12 133 patients, of whom 9901 with type 2 diabetes and additional cardiovascular risk factors were randomly assigned to either dulaglutide (n=4949) or an equal volume of placebo (n=4952). During a median follow-up of 5·4 years, cerebrovascular and other cardiovascular outcomes were ascertained and adjudicated. 158 (3·2%) of 4949 participants assigned to dulaglutide and 205 (4·1%) of 4952 participants assigned to placebo had a stroke during follow-up (hazard ratio [HR] 0·76, 95% CI 0·62–0·94; p=0·010). Dulaglutide reduced ischaemic stroke (0·75, 0·59–0·94, p=0·012) but had no effect on haemorrhagic stroke (1·05, 0·55–1·99; p=0·89). Dulaglutide also reduced the composite of non-fatal stroke or all-cause death (0·88, 0·79–0·98; p=0·017) and disabling stroke (0·74, 0·56–0·99; p=0·042). The degree of disability after stroke did not differ by treatment group. Interpretation: Long-term dulaglutide use might reduce clinically relevant ischaemic stroke in people with type 2 diabetes but does not affect stroke severity. Funding: Eli Lilly and Company.